Ruthenium-containing supramolecular nanoparticles based on bipyridine-modified cyclodextrin and adamantyl PEI with DNA condensation properties - Fang Yan; Jian-Shuang Wu; Zhi-Li Liu; Hong-Li Yu; Yong-Hong Wang; Wei-Fen Zhang; De-Jun Ding (Nanoscale Research Letters, 2018)
Abstract Exploring safe and highly efficient gene carriers made from biocompatible constituents has great prospects for clinical gene therapy. Here, a supramolecular gene delivery system was readily constructed by assembling adamantyl-modified polyethylenimine (PEI-Ada) units with a versatile ruthenium bipyridine-modified cyclodextrin (Ru-CD) through host-guest interactions. The photophysical and morphological features of the PEI-Ada@Ru-CD nanoparticles were systematically characterized by techniques including UV-vis absorption spectroscopy, fluorescence spectroscopy, transmission electron microscopy, dynamic light scattering, and zeta potential experiments. The small size and suitably positive zeta potential of the nanoparticles facilitated their cellular uptake and gene transfection. As expected, DNA interaction studies, which were performed using agarose gel electrophoresis and atomic force microscopy, showed that the ability of the nanoparticles to condense DNA was higher than that of the gold standard, i.e., PEI, at low N/P ratios. The design of these ruthenium-containing supramolecular nanoparticles based on bipyridine-modified cyclodextrin and adamantyl PEI has great prospects in the development of gene delivery vehicles. Graphical abstract